Perlindungan Hukum Penerapan Klausula Eksonerasi pada Perjanjian Investasi Perdagangan Kontrak Berjangka bagi Nasabah di PT Kontak Perkasa Future Pekanbaru berdasarkan UU No 8 Tahun 1999 tentang Perlindungan Konsumen - Ramanitya Dewi Putri; Akel Fernando; Sehoni Sehoni (Lembaga Yasin AlSys, 2026)
Exoneration clauses in standard-form contracts have long been a focus of scholarship in contract law and consumer protection, yet studies that specifically examine their implementation and the implications for legal protection of clients in futures investment trading agreements, particularly in the practices of futures brokerage firms, remain limited. This study aimed to analyze the implementation of exoneration clauses and the forms of legal protection afforded to clients under Law Number 8 of 1999 on Consumer Protection in futures investment trading agreements at PT Kontak Perkasa Futures Pekanbaru. A mixed normative–empirical approach with a descriptive–analytical design was employed, in which data were collected through analysis of investment agreement documents and case studies of client losses, and subsequently examined qualitatively by assessing the alignment between legal norms and investment contract practices. The findings show that futures investment trading agreements are drafted as standard-form contracts containing exoneration clauses, thereby placing clients in a weak bargaining position and encouraging acceptance of the agreements without adequate understanding of their legal consequences. These findings confirm the existence of limitations on the principle of freedom of contract within an inherently asymmetrical legal relationship and reinforce the urgency of legal protection for clients as consumers of futures investment services. The study concludes that strengthening consumer protection in futures investment trading agreements is essential and recommends that regulators and futures brokerage firms review the substance of standard-form contracts to ensure legal certainty and fairness for clients.